REKAM MEDIS (MEDIA EDUKASI DENGAN SOFTWARE) GURU DALAM MENERAPKAN LESSON STUDY - Usman Aripin; Wahyu Setiawan; Heris Hendriana (IKIP SILIWANGI, 2021)
The development of science and technology requires learning activities for the use of technology. The purpose of this training is to introduce MEDICAL can be used in learning the lesson-based studies. The method used is a workshop with the concept of lesson study, where there are three stages, namely plan, do, see. This training is aimed at teachers in the MA Assaidiyah Cipanas. The results of the training, namely the response of the teachers to lesson study were very enthusiastic because they knew the benefits and effectiveness of teaching and learning activities, MEDIS was very efficient and attractive in its use in accordance with the demands of the times, it saved energy, costs, it was easy, it did not need a large room and was easy to distribute.